SURGICAL OUTCOMES OF TOTAL KNEE ARTHROPLASTY USING MOBILE-BEARING IMPLANTS AT VIET DUC UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the surgical outcomes of mobile-bearing total knee arthroplasty performed at Viet Duc University Hospital.Subjects and methods: This study is a case series including six patients with knee osteoarthritis who underwent mobile-bearing total knee arthroplasty at Viet Duc University Hospital. Clinical and functional outcomes were assessed preoperatively and postoperatively.Results: After surgery, the VAS pain score decreased from 7-8/10 points to 1-3/10 points. The KSS increased from 40-45 points preoperatively to 75-85 points postoperatively. Knee range of motion improved markedly, with an average postoperative flexion of 110-115°.Conclusion: Mobile-bearing total knee arthroplasty is a safe and effective treatment for knee osteoarthritis, providing significant pain relief and improvement in knee function.
Keywords: Knee osteoarthritis, total knee arthroplasty, Mobile Bearing, KSS, VAS.